Revision of the Structure and Total Synthesis of Topsentin C - Golantsov, Nikita E.; Festa, Alexey A.; Varlamov, Alexey V.; Voskressensky, Leonid G. (Synthesis, 2017)
An efficient synthetic approach to access (indol-3-yl)ethane-1,2-diamines with a protecting group at the indole N atom from readily available 3-(2-nitrovinyl)indoles is reported. This approach includes solvent-free conjugate addition of O-pivaloylhydroxylamines to 1-Boc-3-(2-nitrovinyl)indoles followed by mild reduction of the adducts. The obtained (indol-3-yl)ethane-1,2-diamines are convenient synthetic precursors for several classes of marine alkaloids. The first total synthesis of racemic topsentin C, a secondary metabolite from Hexadella sp., based on this approach is reported. The initially proposed structure for topsentin C has been revised.
Keywords: bisindole alkaloid; topsentin; hamacanthin; spongotine; diamine; hydroxylamine